Longitudinal study of the interplay between the skin barrier and facial microbiome over 1 year - Seo, Jung Yeon; You, Seung Won; Gu, Ki-Nam; Kim, Hanji; Shin, Joong-Gon; Leem, Sangseob; Hwang, Bo Kyoung; Kim, Yunkwan; Kang, Nae Gyu (Frontiers in Microbiology, 2023)
Skin is a diverse ecosystem that provides a habitat for microorganisms. The skin condition and the skin microbiome interact each other under diverse environmental conditions. This study was conducted on 10 study participants for a one-year, from September 2020 to August 2021, to investigate the variability of skin microbiome and skin biophysical parameters (TEWL, hydration, and elasticity (R5)) according to season, and to understand the interplay between skin microbiome and skin characteristics. We identified that Cutibacterium, Corynebacterium, Staphyloccocus, unclassified genus within Neisseriaceae, and Streptococcus were major skin microbial taxa at the genus level, and fluctuated with the seasons. Cutibacterium was more abundant in winter, while Corynebacterium, Staphylococcus, and Streptococcus were more abundant in summer. Notably, Cutibacterium and skin barrier parameter, TEWL, exhibited a co-decreasing pattern from winter to summer and showed a significant association between Cutibacterium and TEWL. Furthermore, functional profiling using KEGG provided clues on the impact of Cutibacterium on the host skin barrier. This study enhances our understanding of the skin microbiome and its interplay with skin characteristics and highlights the importance of seasonal dynamics in shaping skin microbial composition.